PENGARUH MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN TENDANGAN LURUS PADA KLUB PENCAK SILAT TAPAK SUCI BANDAR JAYA - Nurul Fitria Husin; Joan Siswoyo; Muhammad Fajril Rifaldo; Lungit Wicaksono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of Audio Visual media on straight kick ability at the Tapak Suci Bandarjaya pencak silat club. The study used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 30 students, divided into two groups: the Audio Visual group given Audio Visual Media treatment and the control group without Audio Visual treatment. The measurement instrument used was a pencak silat straight kick ability test. The results showed that there was a significant increase in 1) the Audio Visual group with a Tcount = 15.401> Ttable = 2.145 and p Ttable = 2.048, which means that audio visual media has a more real influence in improving straight kick ability. Based on the results of this study, it can be concluded that audio-visual media is effective and recommended as a training method to stimulate the development of students' psychomotor and cognitive abilities.